Nano-enzyme label of mesoporous silica shell and preparation method and application thereof
Through the nanoenzyme label of mesoporous silica shell, combined with Fe3O4 core and Pt particles, the problem of insufficient sensitivity of existing LFIA to detect influenza A virus is solved, and high-sensitivity influenza A virus detection is achieved, suitable for resource-limited resources environment.
Patent Information
- Application Number
- CN202411552905.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-11-01
AI Technical Summary
Existing colorimetric side-flow immunoassays (LFIA) based on gold nanoparticles have limited sensitivity when detecting influenza A virus and requires specific instruments, which cannot be effectively applied in resource-limited environments.
Using the nanoenzyme tag of mesoporous silica shell, the specific surface area of the complex nanoenzyme is increased by combining Fe3O4 core with mesoporous silica shell and Pt particles, and the specific surface area of the complex nanoenzyme is detected by carboxy chain alkylsulfide-linked influenza A N protein. Antibodies to build high-sensitivity biosensors.
The sensitivity of detecting influenza A virus was significantly improved, and the qualitative and quantitative detection results reached 0.01 and 0.0089 ng·mL-1, which was 100 times higher than that of commercially available LFIA bands based on colloidal gold nanoparticles, and in pharyngeal swab samples. Shows high accuracy and reproducibility.
Smart Images

Figure CN119199105A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of chemical detection, and in particular to a nanozyme label of a mesoporous silica shell and a preparation method and application thereof. Background Art
[0002] Recurrent epidemics of influenza A pose a major public health challenge, particularly affecting vulnerable groups with impaired immune responses, such as the elderly and children. Therefore, emphasis on timely and accurate viral diagnosis is essential for effective management and control. Over the years, diagnostic methods for viral infections have undergone tremendous progress, including traditional enzyme-linked immunosorbent assay (ELISA), immunofluorescence assay (IFA) and polymerase chain reaction (PCR). Among these methods, real-time reverse transcription polymerase chain reaction (RT-PCR) is generally considered to be the ultimate benchmark for identifying influenza viruses. However, the use of RT-PCR usually requires professional techniques and complex laboratory instruments, limiting its large-scale application in rapid field diagnosis. Therefore, there is increasing interest in the development and implementation of point-of-care testing.
[0003] Lateral flow immunoassay (LFIA) is the most commonly used platform for point-of-care testing (POCT) due to its significant advantages in affordability, real-time analysis, mobility, and user-friendly operation. In particular, colorimetric LFIA (C-LFIA) has attracted considerable interest due to its easy visual identification and suitability for resource-limited settings. However, conventional gold nanoparticle (AuNP)-based colorimetric LFIA has limitations in its sensitivity. In recent years, the emergence of innovative detection methods has improved the sensitivity of LFIA, including fluorescence technology, photothermal technology, and surface-enhanced Raman scattering (SERS) technology. However, these tests often require specific instrumentation, making them infeasible for application in resource-limited settings.
[0004] Nanozymes combine the stability of nanomaterials with the catalytic activity of natural enzymes and are used in colorimetric amplification LFIA (CA-LFIA) through catalytic reactions with specific enzyme substrates. Today, common types of nanozymes include precious metals (Au, Pt, and Cu), metal oxides (Fe3O4, MnO2, and TiO2), and carbon materials (such as carbon nanotubes and graphene). Among these nanomaterials, the magnetic separation process based on Fe3O4 composite nanozymes can more effectively recover the target analytes.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] The object of the present invention is to provide a nanozyme tag with a mesoporous silica shell and a preparation method and application thereof. The nanozyme tag with a mesoporous silica shell further improves the performance of the biosensor and prepares a mesoporous structure to increase the specific surface area of the composite nanozyme.
[0007] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted: In a first aspect, the present invention provides a nanozyme tag of a mesoporous silica shell, wherein the nanozyme tag of the mesoporous silica shell comprises a Fe3O4 core and a mesoporous silica shell coated on the surface of the Fe3O4 core; The voids in the mesoporous silica shell are filled with Pt particles, and antibodies for detecting influenza A N protein are connected to the Pt particles via carboxyl alkane sulfide.
[0008] Preferably, the particle size of the Fe3O4 core is 95~105 nm.
[0009] Preferably, the thickness of the mesoporous silica shell is 15-25 nm.
[0010] Preferably, the specific surface area of the mesoporous silica shell is 60-62 m 2 ·g -1 .
[0011] Preferably, the average mesopore size of the mesoporous silica shell is 4.8-4.9 nm.
[0012] Preferably, the total pore volume of the mesoporous silica shell is 0.12-0.14 cm 3 ·g -1 .
[0013] Preferably, the particle size of the Pt particles is 3-6 nm.
[0014] Preferably, the carboxyalkane sulfide is 11-mercaptoundecanoic acid (MUA).
[0015] In a second aspect, the present invention provides a method for preparing a nanozyme tag of a mesoporous silica shell as described in the first aspect, the preparation method comprising: (1) dispersing Fe3O4 nanoparticles in an ethanol aqueous solution containing a dispersant, performing a first ultrasonic treatment, adding a catalyst, performing a second ultrasonic treatment, adding an organic silicone grease solution, performing a third ultrasonic treatment, and then coating the surface of the Fe3O4 nanoparticles with a silica shell to obtain Fe3O4@SiO2; (2) resuspending the Fe3O4@SiO2 in an aqueous solution containing a dispersant, adding a base and stirring to etch the silica shell to form a mesoporous silica shell, and collecting the product by magnetic separation to obtain Fe3O4@MSiO2; (3) mixing the Fe3O4@MSiO2, dispersant and chloroplatinic acid in an ethanol aqueous solution, performing a first stirring, adding a reducing agent, and performing a second stirring to deposit Pt particles in the voids of the mesoporous silica shell to obtain Fe3O4@MSiO2@Pt nanozyme; (4) mixing the Fe3O4@MSiO2@Pt nanozyme and carboxyl alkane sulfide in ethanol and subjecting them to ultrasonic treatment to connect the carboxyl alkane sulfide to the Pt particles, thereby obtaining Fe3O4@MSiO2@Pt-MUA seeds; (5) Dispersing the Fe3O4@MSiO2@Pt-MUA seeds in MEST buffer, performing the first ultrasonic treatment, and adding N -hydroxysuccinimide solution and carbodiimide solution, perform a second ultrasonic treatment to obtain a mixture; disperse the mixture in PBS buffer, add influenza A N protein detection antibody, incubate, add bovine serum albumin solution to block non-binding sites, collect the product by a magnet, and obtain the nanozyme label of the mesoporous silica shell.
[0016] Preferably, in step (1), the dispersant is polyvinyl pyrrolidone K40; the catalyst is NH4OH; and the organic silicone grease is tetraethoxysilane.
[0017] Preferably, in step (1), the volume ratio of the Fe3O4 nanoparticles, ethanol and water is (0.4-0.8):(30-50):(3-7); wherein the volume mass ratio of the Fe3O4 nanoparticles and the dispersant is (0.4-0.8) mL:(10-30) mg.
[0018] Preferably, in step (1), the volume ratio of the Fe3O4 nanoparticles, the catalyst and the silicone grease solution is (1.7-3.7):(3.4-6.4):1; wherein the concentration of the silicone grease solution is 0.9-1.0 g·mL -1 .
[0019] Preferably, in step (1), the power of the first ultrasonic treatment, the second ultrasonic treatment and the third ultrasonic treatment are each independently 60-100 W.
[0020] Preferably, in step (1), the time of the first ultrasonic treatment is 1 to 10 min; the time of the second ultrasonic treatment is 20 to 40 min; and the time of the third ultrasonic treatment is 20 to 40 min.
[0021] Preferably, step (1) further comprises the following post-treatment: washing the Fe3O4@SiO2 with ethanol and then resuspending it in ethanol; wherein the concentration of the Fe3O4@SiO2 is 5-10 µM.
[0022] Preferably, in step (2), the dispersant is polyvinyl pyrrolidone K15; and the alkali is sodium hydroxide solution.
[0023] Preferably, the concentration of the sodium hydroxide solution is 0.25-0.35 g / mL.
[0024] Preferably, in step (2), the mass ratio of the Fe3O4@SiO2, dispersant and alkali is 1:(40~60):(300~500); the volume ratio of the Fe3O4@SiO2 and water is 1:(1~5).
[0025] Preferably, in step (2), the stirring speed is 500-550 rpm, and the stirring time is 4-8 h.
[0026] Preferably, step (2) further comprises the following post-treatment: washing the Fe3O4@MSiO2 with water and ethanol.
[0027] Preferably, in step (3), the dispersant is polyvinyl pyrrolidone K40; and the reducing agent is sodium borohydride.
[0028] Preferably, in step (3), the volume ratio of Fe3O4@MSiO2, reducing agent and chloroplatinic acid is 100:(7-9):(4-6).
[0029] Preferably, in step (3), the mass volume ratio of the Fe3O4@MSiO2 and the ethanol aqueous solution is (2-4) mg:(40-60) mL; wherein the volume ratio of the ethanol and water is (10-30):(20-40).
[0030] Preferably, in step (3), the rotation speeds of the first stirring and the second stirring are respectively 500-550 rpm.
[0031] Preferably, in step (3), the first stirring time is 10 to 20 min; the second stirring time is 10 to 30 min.
[0032] Preferably, step (3) further comprises the following post-treatment: washing the Fe3O4@MSiO2@Pt nanozyme with ethanol and then resuspending it in ethanol; wherein the volume ratio of the Fe3O4@MSiO2@Pt nanozyme to ethanol is 1:(1-5).
[0033] Preferably, in step (4), the carboxyalkane sulfide is 11-mercaptoundecanoic acid.
[0034] Preferably, in step (4), the volume ratio of the Fe3O4@MSiO2@Pt nanozyme to the carboxyl alkane sulfide is (100-300):1.
[0035] Preferably, in step (4), the final concentration of the carboxyl alkane sulfide is 8-12 mM.
[0036] Preferably, in step (4), the power of the ultrasonic treatment is 60-100 W, and the time of the ultrasonic treatment is 0.5-2 h.
[0037] Preferably, in step (5), the Fe3O4@MSiO2@Pt-MUA seeds, N The volume ratio of the -hydroxysuccinimide solution to the carbodiimide solution is (150~250):1:(4~6).
[0038] Preferably, the N The concentration of the -hydroxysuccinimide solution is 90~110 mM.
[0039] Preferably, the concentration of the carbodiimide solution is 9-11 mM.
[0040] Preferably, in step (5), the volume ratio of the mixture, influenza A N protein detection antibody and bovine serum albumin is (330-334):1:(90-120).
[0041] Preferably, in step (5), the power of the first ultrasonic treatment and the second ultrasonic treatment are each independently 60-100 W.
[0042] Preferably, in step (5), the time of the first ultrasonic treatment is 20 to 40 s; and the time of the second ultrasonic treatment is 10 to 20 min.
[0043] Preferably, in step (5), the incubation time is 140 to 160 min.
[0044] Preferably, step (5) further comprises the following post-treatment: resuspending the product collected by the magnet in a PBST solution.
[0045] In a third aspect, the present invention provides a use of a nanozyme tag with a mesoporous silica shell as described in the first aspect in preparing a biosensor for detecting influenza A virus.
[0046] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention establishes a lateral flow immunoassay (LFIA) for detecting influenza A (Flu A) using a "three-in-one" multifunctional mesoporous silica shell nanozyme tag; the nanozyme tag uses Fe3O4 as the core, is wrapped by mesoporous silica to form Fe3O4@MSiO2, and Pt particles are filled in the voids of the mesoporous silica shell. The advantages of the composite nanozyme are as follows: (a) Using Fe3O4 as the core magnetic core, the nanozyme has a fast magnetic separation ability, which significantly simplifies the preparation and operation process; (b) The thickness of the mesoporous silica is controllable, and it has good stability and a large specific surface area; (c) The loading amount of Pt particles is increased by the mesoporous structure with a large specific surface area, thereby improving the POD-like activity, thereby significantly improving the POD-like activity, thereby improving the detection sensitivity.
[0047] (2) The present invention is the first to couple mesoporous silica shell nanozyme tags with specific antibodies, which can be used to construct CA-LFIA strips to detect influenza A virus. Compared with previously reported catalytically active materials, the designed composite nanozyme has a larger specific surface area due to the introduction of MSiO2, which allows more Pt particles to grow on its surface to improve the catalytic performance.
[0048] (3) After the colorimetric catalysis of the nanozyme tag of the mesoporous silica shell of the present invention, the qualitative and quantitative detection results of the nanozyme tag for influenza A N protein were reduced to 0.01 and 0.0089 ng·mL -1 , which is approximately 100 times more sensitive than commercially available colloidal gold nanoparticle (AuNP)-based LFIA strips; for the detection of inactivated H1N1 virus, quantification can be as low as 33 copies·mL -1 .
[0049] (4) The present invention applies the nanozyme tag of the mesoporous silica shell to the analysis of throat swab samples, and shows high accuracy and reproducibility in the throat swab sample simulation experiment. The "three-in-one" multifunctional nanozyme can quickly, specifically and sensitively detect influenza A virus, and has great potential in virus POCT diagnosis. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0051] Figure 1 The figure is a schematic diagram of the process for preparing the nanozyme tag of the mesoporous silica shell of the present invention.
[0052] Figure 2A HRTEM image of Fe3O4@SiO2 provided in Example 1.
[0053] Figure 2B HRTEM image of Fe3O4@MSiO2 provided in Example 1.
[0054] Figure 2C HRTEM image of Fe3O4@MSiO2@Pt provided in Example 1.
[0055] Figure 2D This is a locally enlarged HRTEM image of Fe3O4@SiO2 provided in Example 1.
[0056] Figure 2E This is a locally enlarged HRTEM image of Fe3O4@MSiO2 provided in Example 1.
[0057] Figure 2F This is a locally enlarged HRTEM image of Fe3O4@MSiO2@Pt provided in Example 1.
[0058] Figure 2G Hysteresis curves of Fe3O4, Fe3O4@MSiO2 and Fe3O4@MSiO2@Pt provided in Example 1.
[0059] Figure 2H The nitrogen adsorption isotherm and pore size distribution analysis diagram of Fe3O4@MSiO2 provided in Example 1.
[0060] Fig.2I This is an elemental surface scanning diagram of Fe3O4@MSiO2@Pt provided in Example 1.
[0061] Figure 2J XRD patterns of Fe3O4, Fe3O4@MSiO2, and Fe3O4@MSiO2@Pt provided in Example 1.
[0062] Figure 2KHigh-resolution spectrum of Fe, O, Si and Pt of Fe3O4@MSiO2@Pt provided in Example 1.
[0063] Figure 3 The corresponding absorbance graph of Fe3O4@MSiO2@Pt generated by reducing chloroplatinic acid of different concentrations provided in Example 2.
[0064] Figure 4A This is a diagram of the catalytic activity of Fe3O4@MSiO2@Pt in different concentrations of color developing solutions provided in Example 3.
[0065] Figure 4B A comparison chart of the enzyme kinetic curves of Fe3O4 and Fe3O4@MSiO2@Pt provided in Example 3 when TMB is used as a substrate.
[0066] Figure 4C A comparison chart of the enzyme kinetic curves of Fe3O4 and Fe3O4@MSiO2@Pt provided in Example 3 when H2O2 is used as a substrate.
[0067] Figure 4D ESR spectra of Fe3O4@Pt, Fe3O4@SiO2@Pt and Fe3O4@MSiO2@Pt provided in Example 3.
[0068] Figure 5 This is an experimental flow chart of the multimodal immunochromatography technology driven by the mesoporous silica shell nanozyme tag provided in Application Example 1 for detecting influenza A.
[0069] Fig. 6A Optimization results of capture antibody concentration provided for Application Example 1.
[0070] Figure 6B This is the optimization result diagram of the Fe3O4@MSiO2@Pt immune label addition amount provided for Application Example 1.
[0071] Figure 6C This is a graph showing the optimization results of the reaction time provided for Application Example 1.
[0072] Fig. 7A The colorimetric and catalytically enhanced colorimetric results of the Fe3O4@MSiO2@Pt-LFIA platform provided in Application Example 1 for detecting different concentrations of Flu A-NPs.
[0073] Figure 7B The colorimetric and catalytically enhanced colorimetric results of the Fe3O4@SiO2@Pt-LFIA platform provided in Application Example 1 for detecting different concentrations of Flu A-NPs.
[0074] Figure 7CThe test results of the commercial AuNP-LFIA test strip provided for Application Example 1.
[0075] Fig.7D Calibration curve of the Fe3O4@MSiO2@Pt-LFIA platform provided in Application Example 1 for the detection of Flu A-NPs of different concentrations.
[0076] Fig. 7E Bar graph of the Fe3O4@SiO2@Pt-LFIA platform provided in Application Example 1 for the detection of different concentrations of Flu A-NPs.
[0077] Figure 7F Specific detection results of the Fe3O4@MSiO2@Pt-LFIA platform provided for Application Example 1.
[0078] Figure 7G The repeatability test results of the Fe3O4@MSiO2@Pt-LFIA platform provided for Application Example 1.
[0079] Fig. 8A The colorimetric and catalytic enhanced colorimetric results of the Fe3O4@MSiO2@Pt-LFIA platform provided in Application Example 1 for detecting different concentrations of H1N1 inactivated virus.
[0080] Figure 8B The calibration curve of the Fe3O4@MSiO2@Pt-LFIA platform provided in Application Example 1 for detecting H1N1 inactivated viruses at different concentrations. DETAILED DESCRIPTION
[0081] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0082] It should be noted that specific details are described in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in a variety of other ways different from those described herein, and those skilled in the art can make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0083] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0084] In a first aspect, the present invention provides a nanozyme tag with a mesoporous silica shell, such as Figure 1 As shown, the mesoporous silica shell nanozyme tag includes a Fe3O4 core and a mesoporous silica shell coated on the surface of the Fe3O4 core; The voids in the mesoporous silica shell are filled with Pt particles, and the Pt particles are connected to influenza A N protein detection antibodies (Influenza A N-protein detection antibody, Catalog# 20221124-2) via carboxyl alkane sulfide.
[0085] In the present invention, a "three-in-one" multifunctional mesoporous silica shell nanozyme tag is used; the nanozyme tag uses Fe3O4 as the core, is wrapped by mesoporous silica to form Fe3O4@MSiO2, and Pt particles are filled in the voids of the mesoporous silica shell, and then the Pt particles and influenza A N protein detection antibodies are connected by carboxyl alkane sulfide. The advantages of this composite nanozyme are as follows: (a) Fe3O4 is used as the core magnetic core, so that the nanozyme has a fast magnetic separation ability, which significantly simplifies the preparation and operation process; (b) The thickness of mesoporous silica is controllable, with good stability and a large specific surface area; (c) The loading amount of Pt particles is increased by the mesoporous structure with a large specific surface area, and the POD-like activity is improved, so as to significantly improve the POD-like activity, thereby improving the detection sensitivity.
[0086] As an optional embodiment, the particle size of the Fe3O4 core is 95~105 nm, for example, it can be 95 nm, 96 nm, 98 nm, 100 nm, 102 nm, 104 nm, 105 nm, etc.
[0087] As an optional embodiment, the thickness of the mesoporous silica shell is 15-25 nm, for example, it can be 15 nm, 16 nm, 18 nm, 20 nm, 22 nm, 24 nm, 25 nm, etc.
[0088] As an optional embodiment, the specific surface area of the mesoporous silica shell is 60-62 m 2 ·g -1 , for example, it could be 60 m 2 ·g -1、60.5 m 2 ·g -1 、61 m 2 ·g -1 、61.5 m 2 ·g -1 、62 m 2 ·g -1 wait.
[0089] As an optional embodiment, the average mesopore size of the mesoporous silica shell is 4.8-4.9 nm, for example, 4.8 nm, 4.82 nm, 4.84 nm, 4.86 nm, 4.88 nm, 4.9 nm, etc.
[0090] As an optional embodiment, the total pore volume of the mesoporous silica shell is 0.12-0.14 cm 3 ·g -1 , for example, it can be 0.12 cm 3 ·g -1 , 0.125 cm 3 ·g -1 , 0.13 cm 3 ·g -1 , 0.135 cm 3 ·g -1 , 0.14 cm 3 ·g -1 wait.
[0091] As an optional embodiment, the particle size of the Pt particles is 3 to 6 nm, for example, it can be 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm, 5.5 nm, 6 nm, etc.
[0092] As an optional embodiment, the carboxyalkane sulfide is 11-mercaptoundecanoic acid (MUA).
[0093] In a second aspect, the present invention provides a method for preparing a nanozyme tag of a mesoporous silica shell as described in the first aspect, such as Figure 1 As shown, the preparation method comprises: (1) dispersing Fe3O4 nanoparticles in an ethanol aqueous solution containing a dispersant, performing a first ultrasonic treatment, adding a catalyst, performing a second ultrasonic treatment, adding an organic silicone grease solution, performing a third ultrasonic treatment, and then coating the surface of the Fe3O4 nanoparticles with a silica shell to obtain Fe3O4@SiO2; (2) resuspending the Fe3O4@SiO2 in an aqueous solution containing a dispersant, adding a base and stirring to etch the silica shell to form a mesoporous silica shell, and collecting the product by magnetic separation to obtain Fe3O4@MSiO2; (3) mixing the Fe3O4@MSiO2, dispersant and chloroplatinic acid in an ethanol aqueous solution, performing a first stirring, adding a reducing agent, and performing a second stirring to deposit Pt particles in the voids of the mesoporous silica shell to obtain Fe3O4@MSiO2@Pt nanozyme; (4) mixing the Fe3O4@MSiO2@Pt nanozyme and carboxyl alkane sulfide in ethanol and subjecting them to ultrasonic treatment to connect the carboxyl alkane sulfide to the Pt particles, thereby obtaining Fe3O4@MSiO2@Pt-MUA seeds; (5) Dispersing the Fe3O4@MSiO2@Pt-MUA seeds in MEST buffer, performing the first ultrasonic treatment, and adding N -hydroxysuccinimide solution and carbodiimide solution, perform a second ultrasonic treatment to obtain a mixture; disperse the mixture in PBS buffer, add influenza A N protein detection antibody, incubate, add bovine serum albumin solution to block non-binding sites, collect the product by a magnet, and obtain the nanozyme label of the mesoporous silica shell.
[0094] As an optional implementation, in step (1), the dispersant is polyvinyl pyrrolidone K40 (PVP-K40); the catalyst is NH4OH; and the organic silicone grease is tetraethoxysilane (TEOS).
[0095] As an optional embodiment, in step (1), the volume ratio of the Fe3O4 nanoparticles, ethanol and water is (0.4~0.8):(30~50):(3~7); wherein, "0.4~0.8" can be, for example, 0.4, 0.5, 0.6, 0.7, 0.8, etc.; "30~50" can be, for example, 30, 35, 40, 45, 50, etc.; "3~7" can be, for example, 3, 4, 5, 6, 7, etc.
[0096] As an optional embodiment, in step (1), the volume mass ratio of the Fe3O4 nanoparticles and the dispersant is (0.4~0.8) mL:(10~30) mg; wherein, "0.4~0.8" can be, for example, 0.4, 0.5, 0.6, 0.7, 0.8, etc.; "10~30" can be, for example, 10, 15, 20, 25, 30, etc.
[0097] As an optional embodiment, in step (1), the volume ratio of the Fe3O4 nanoparticles, the catalyst and the silicone grease solution is (0.4-0.8):(1.0-1.5):(0.20-0.25); wherein, "0.4-0.8" can be, for example, 0.4, 0.5, 0.6, 0.7, 0.8, etc.; "1.0-1.5" can be, for example, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, etc.; "0.20-0.25" can be, for example, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, etc.
[0098] As an optional embodiment, the concentration of the organic silicone grease solution is 0.9-1.0 g·mL -1 , for example, it can be 0.9 g·mL -1 , 0.92 g·mL -1 , 0.94 g·mL -1 , 0.96 g·mL -1 , 0.98 g·mL -1 , 1.0 g mL -1 wait.
[0099] As an optional embodiment, in step (1), the power of the first ultrasonic treatment, the second ultrasonic treatment and the third ultrasonic treatment are each independently 60 to 100 W, for example, 60 W, 65 W, 70 W, 75 W, 80 W, 85 W, 90 W, 95 W, 100 W, etc.
[0100] As an optional embodiment, in step (1), the time of the first ultrasonic treatment is 1 to 10 min, for example, it can be 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min, 10 min, etc.
[0101] As an optional embodiment, in step (1), the time of the second ultrasonic treatment is 20 to 40 min, for example, it can be 20 min, 25 min, 30 min, 35 min, 40 min, etc.
[0102] As an optional embodiment, in step (1), the duration of the third ultrasonic treatment is 20 to 40 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, etc.
[0103] As an optional embodiment, step (1) further includes the following post-treatment: washing the Fe3O4@SiO2 with ethanol and then resuspending it in ethanol to obtain an ethanol solution of Fe3O4@SiO2.
[0104] As an optional embodiment, in step (1), the number of washing times is more than one time, for example, it can be one time, two times, three times, four times, five times, etc.
[0105] As an optional embodiment, in step (1), the concentration of Fe3O4@SiO2 in the ethanol solution of the resuspended Fe3O4@SiO2 is 5-10 µM, for example, 5 µM, 6 µM, 7 µM, 8 µM, 9 µM, 10 µM, etc.
[0106] As an optional embodiment, in step (2), the dispersant is polyvinyl pyrrolidone K15 (PVP-K15); and the base is sodium hydroxide solution.
[0107] As an optional embodiment, in step (2), the mass ratio of Fe3O4@SiO2, dispersant and alkali is 1:(40~60):(300~500); wherein, "40~60" can be, for example, 40, 45, 50, 55, 60, etc.; "300~500" can be, for example, 300, 350, 400, 450, 500, etc.
[0108] As an optional embodiment, the concentration of the sodium hydroxide solution is 0.25~0.35 g / mL, for example, it can be 0.25 g / mL, 0.26 g / mL, 0.27 g / mL, 0.28 g / mL, 0.29 g / mL, 0.30 g / mL, 0.31 g / mL, 0.32 g / mL, 0.33 g / mL, 0.34 g / mL, 0.35 g / mL, etc.
[0109] As an optional implementation, in step (2), the volume ratio of Fe3O4@SiO2 to water is 1:(1-5), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, etc.
[0110] As an optional embodiment, in step (2), the stirring speed is 500-550 rpm, for example, it can be 500 rpm, 510 rpm, 520 rpm, 530 rpm, 540 rpm, 550 rpm, etc.
[0111] As an optional embodiment, in step (2), the stirring time is 4 to 8 h, for example, it can be 4 h, 4.5 h, 5 h, 5.5 h, 6 h, 6.5 h, 7 h, 7.5 h, 8 h, etc.
[0112] As an optional implementation, step (2) further includes the following post-treatment: washing the Fe3O4@MSiO2 with water and ethanol.
[0113] As an optional embodiment, in step (2), the number of washing times is more than one time, for example, it can be one time, two times, three times, four times, five times, etc.
[0114] As an optional embodiment, in step (3), the dispersant is polyvinyl pyrrolidone K40 (PVP-K40); and the reducing agent is sodium borohydride (NaBH4).
[0115] As an optional embodiment, in step (3), the volume ratio of Fe3O4@MSiO2, reducing agent and chloroplatinic acid is 100:(7~9):(4~6); wherein the reducing agent "7~9" can be, for example, 7, 7.5, 8, 8.5, 9, etc.; wherein the chloroplatinic acid "4~6" can be, for example, 4, 4.5, 5, 5.5, 6, etc.
[0116] As an optional embodiment, in step (3), the mass volume ratio of the Fe3O4@MSiO2 and the ethanol aqueous solution is (2~4) mg:(40~60) mL; wherein "2~4" can be, for example, 2, 2.5, 3, 3.5, 4, etc.; wherein "40~60" can be, for example, 40, 45, 50, 55, 60, etc.
[0117] As an optional embodiment, in step (3), the volume ratio of ethanol to water is (10-30):(20-40); wherein "10-30" can be, for example, 10, 15, 20, 25, 30, etc.; wherein "20-40" can be, for example, 20, 25, 30, 35, 40, etc.
[0118] As an optional embodiment, in step (3), the rotation speeds of the first stirring and the second stirring are each 500-550 rpm, for example, 500 rpm, 510 rpm, 520 rpm, 530 rpm, 540 rpm, 550 rpm, etc.
[0119] As an optional embodiment, in step (3), the first stirring time is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, etc.
[0120] As an optional embodiment, in step (3), the second stirring time is 10 to 30 min, for example, it can be 10 min, 12 min, 14 min, 16 min, 18 min, 20 min, 22 min, 24 min, 26 min, 28 min, 30 min, etc.
[0121] As an optional embodiment, step (3) further includes the following post-treatment: washing the Fe3O4@MSiO2@Pt nanozyme with ethanol and then resuspending it in ethanol to obtain an ethanol solution of Fe3O4@MSiO2@Pt nanozyme.
[0122] As an optional embodiment, in step (3), the number of washing times is more than one time, for example, it can be one time, two times, three times, four times, five times, etc.
[0123] As an optional embodiment, in step (3), in the ethanol solution of the resuspended Fe3O4@MSiO2@Pt nanozyme, the volume ratio of the Fe3O4@MSiO2@Pt nanozyme to ethanol is 1:(1~5), for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:4, etc.
[0124] As an optional embodiment, in step (4), the carboxyl alkane sulfide is 11-mercaptoundecanoic acid (MUA).
[0125] As an optional embodiment, in step (4), the volume ratio of the Fe3O4@MSiO2@Pt nanozyme and the carboxyl alkane sulfide is (100~300):1, for example, it can be 100:1, 120:1, 140:1, 160:1, 180:1, 200:1, 220:1, 240:1, 260:1, 280:1, 300:1, etc.
[0126] As an optional embodiment, in step (4), the final concentration of the carboxyl alkane sulfide is 8-12 mM, for example, 8 mM, 8.5 mM, 9 mM, 9.5 mM, 10 mM, 10.5 mM, 11 mM, 11.5 mM, 12 mM, etc.
[0127] As an optional embodiment, in step (4), the power of the ultrasonic treatment is 60-100 W, for example, it can be 60 W, 65 W, 70 W, 75 W, 80 W, 85 W, 90 W, 95 W, 100 W, etc.
[0128] As an optional embodiment, in step (4), the ultrasonic treatment time is 0.5 to 2 h, for example, it can be 0.5 h, 0.6 h, 0.8 h, 1 h, 1.2 h, 1.4 h, 1.6 h, 1.8 h, 2 h, etc.
[0129] As an optional embodiment, in step (5), the Fe3O4@MSiO2@Pt-MUA seeds, N The volume ratio of the -hydroxysuccinimide solution to the carbodiimide solution is (150-250):1:(4-6), for example, it can be 150:1:4, 170:1:4.4, 190:1:4.8, 210:1:5.2, 230:1:5.6, 250:1:6, etc.
[0130] As an optional implementation, the N The concentration of the -hydroxysuccinimide solution is 90-110 M, for example, it can be 90 mM, 92 mM, 94 mM, 96 mM, 98 mM, 100 mM, 102 mM, 104 mM, 106 mM, 108 mM, 110 mM, etc.
[0131] As an optional embodiment, the concentration of the carbodiimide solution is 9~11 M, for example, it can be 9 mM, 9.2 mM, 9.4 mM, 9.5 mM, 9.6 mM, 9.8 mM, 10 mM, 10.2 mM, 10.4 mM, 10.5 mM, 10.6 mM, 10.8 mM, 11 mM, etc.
[0132] As an optional embodiment, in step (5), the volume ratio of the mixture, influenza A N protein detection antibody and bovine serum albumin is (330-334):1:(90-120); wherein "330-334" can be, for example, 330, 331, 332, 333, 334, etc.; wherein "90-120" can be, for example, 90, 96, 102, 108, 114, 120, etc.
[0133] As an optional embodiment, in step (5), before dispersing the mixture in PBS buffer, the mixture needs to be washed with PBST.
[0134] As an optional embodiment, in step (5), the power of the first ultrasonic treatment and the second ultrasonic treatment are each independently 60 to 100 W, for example, 60 W, 65 W, 70 W, 75 W, 80 W, 85 W, 90 W, 95 W, 100 W, etc.
[0135] As an optional embodiment, in step (5), the time of the first ultrasonic treatment is 20 to 40 s, for example, it can be 20 s, 25 s, 30 s, 35 s, 40 s, etc.
[0136] As an optional embodiment, in step (5), the time of the second ultrasonic treatment is 10 to 20 min, for example, it can be 10 min, 11 min, 12 min, 13 min, 14 min, 15 min, 16 min, 17 min, 18 min, 19 min, 20 min, etc.
[0137] As an optional embodiment, in step (5), the incubation time is 140-160 min, for example, it can be 140 min, 145 min, 150 min, 155 min, 160 min, etc.
[0138] As an optional embodiment, step (5) further includes the following post-treatment: resuspending the product collected by the magnet in a PBST solution.
[0139] In a third aspect, the present invention provides a use of a nanozyme tag with a mesoporous silica shell as described in the first aspect in preparing a biosensor for detecting influenza A virus.
[0140] In a fourth aspect, the present invention provides an immunochromatographic test paper for detecting influenza A virus, the immunochromatographic test paper comprising a nitrocellulose membrane, a detection line T line and a quality control line C line being arranged on the nitrocellulose membrane; wherein the detection line T line is coated with an influenza A N-protein capture antibody (Influenza A N-protein capture antibody; Catalog# 20230228-2). wherein the quality control line C line is coated with a goat anti-mouse IgG antibody (Goat Anti-Mouse IgG).
[0141] In a fifth aspect, the present invention provides a method for detecting influenza A virus, the method for detecting influenza A virus comprising the following steps: Formation of S1, Fe3O4@MSiO2@Pt-Flu A complex: The nanozyme tag of the mesoporous silica shell of the first aspect is mixed with a solution containing influenza A virus to form a Fe3O4@MSiO2@Pt-Flu A complex, and the product is collected by magnetic separation.
[0142] S2. Qualitative analysis: The Fe3O4@MSiO2@Pt-Flu A complex is added to the sample pad of the immunochromatographic test paper described in the fourth aspect, so that the complex moves along the direction of the absorbent pad under capillary action; in this step, a portion of the Fe3O4@MSiO2@Pt-Flu A complex binds to the influenza A N protein capture antibody on the detection line T line to form a Fe3O4@MSiO2@Pt-Flu A-mAbs sandwich structure, producing a black band for initial qualitative analysis; the excess Fe3O4@MSiO2@Pt-Flu A complex continues to flow forward along the immune marker and is captured on the quality control line.
[0143] S3. Quantitative analysis: The colorimetric amplification DAB solution is dropped onto the T line to cause the nanozyme tag to undergo a catalytic reaction to generate oxidized DAB (ox-DAB) with a brown precipitate. In this step, the colorimetric amplification results can be visually identified or quantitatively evaluated through photos taken with a smartphone, and then the grayscale intensity value corresponding to the test line area can be extracted using Image J.
[0144] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0145] Example 1 This embodiment provides a nanozyme tag with a mesoporous silica shell, and the nanozyme tag with a mesoporous silica shell is prepared by the following steps: (1) Preparation of Fe3O4@SiO2: 600 μL of 100 nm Fe3O4 nanoparticles were dispersed in a solution containing 40 mL of ethanol, 5 mL of water and 20 mg of PVPK40 and sonicated at 80 W for 5 min. Then, 1.2 mL of NH4OH was added and sonicated at 80 W for 30 min. 220 μL of TEOS solution (26 wt%) was added and sonicated at 80 W for 30 min. The final product was collected by magnetic separation and washed three times with ethanol. Then, the prepared Fe3O4@SiO2 was resuspended in 5 mL of ethanol solution.
[0146] (2) Preparation of mesoporous silica shell: 3 mg of Fe3O4@SiO2 was resuspended in deionized water, and 150 mg of PVP K15 was added. The mixture was stirred briefly, and then 4 mL of sodium hydroxide solution (0.3 g mL -1) was added to the mixture and stirred continuously at 26 °C and 500 rpm for 6 h. The final product was then collected by magnetic separation and subsequently rinsed with deionized water and ethanol three times to obtain Fe3O4@MSiO2.
[0147] (3) Loading of Pt particles: 3 mg of Fe3O4@MSiO2, 20 mg of PVP K40 and 400 μL of H2PtCl6 solution (1 wt%) were mixed in 50 mL of solution (20 mL of ethanol and 30 mL of deionized water) and stirred at 500 rpm for 15 min. Then 250 μL of NaBH4 solution (0.1 M) was quickly added to the solution and stirred at 500 rpm for 20 min to deposit Pt particles in the voids of the mesoporous silica shell. During this process, the color of the reaction mixture quickly changed from dark yellow to black. The final product was then collected by magnetic separation. Finally, the product was washed with ethanol and the prepared Fe3O4@MSiO2@Pt nanozyme was resuspended in 5 mL of ethanol solution.
[0148] (4) MUA connection: The MUA solution with a final concentration of 10 μM was added to the Fe3O4@MSiO2@Pt nanozyme solution at one time, and ultrasonicated at a power of 80 W for 1 h to connect the carboxyl alkane sulfide to the Pt particles to obtain Fe3O4@MSiO2@Pt-MUA seeds.
[0149] (5) Preparation of nanozyme tags with mesoporous silica shells: 2 mL of Fe3O4@MSiO2@Pt-MUA seeds were washed with PBST (0.05%), dispersed in 500 μL of MEST buffer (10 mM, pH 5.5), and sonicated at 80 W for 30 s. Subsequently, 10 μL of freshly prepared NHS (100 mM) and 50 μL of EDC (10 mM) were added, and the carboxyl groups were activated by sonication at 80 W for 15 min to obtain a mixture. Then, the mixture was dispersed in 500 μL of PBS buffer (10 mM, pH 7.4), and 13 μg of influenza A N protein detection antibody was added, and incubated at 26 °C for 150 min. At the same time, in order to block the non-binding sites, 150 μL of BSA solution (10 mg mL -1 ), and finally the product was collected by a magnet and resuspended in 120 μL of PBST (0.05%) solution for further use at 4 °C.
[0150] Test Example 1 Characterization of Nanozyme Tags with Mesoporous Silica Shells Test sample: the test sample provided in Example 1; Test methods: High-resolution transmission electron microscopy (HRTEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were investigated.
[0151] Test results: I. HRTEM test results: The morphology of Fe3O4@SiO2, Fe3O4@MSiO2 and the nanozyme tags of the mesoporous silica shell was determined by HRTEM. Figure 2A , Figure 2B and Figure 2C The core-shell structure of the nanoparticles is depicted, with the Fe3O4 cores represented by black spheres with an average size of about 100 nm; meanwhile, the silica shells ( Figure 2D ), and this observation confirmed that the Fe3O4NPs were successfully encapsulated in the nonporous silica shell. Furthermore, from the corresponding magnified HRTEM image ( Figure 2E ), after SiO2 is treated under alkaline conditions, the non-porous silica shell is selectively etched to show an obvious wormhole-like mesoporous structure. The present invention calculates the BET specific surface area of magnetic mesoporous silica nanoparticles to be 61.46 m 2 ·g -1 , with an average mesopore size of 4.85 nm and a total pore volume of 0.13 cm 3 ·g -1 . Furthermore, from the corresponding HRTEM images ( Figure 2F ) showed that a large number of well-distributed Pt particles were in situ synthesized on mesoporous SiO2, and the Pt particles were deposited in the voids of the mesoporous silica shell. The high specific surface area of the mesoporous structure can significantly increase the loading amount of Pt particles, thereby enhancing the catalytic activity.
[0152] II. Superparamagnetic properties test results: The superparamagnetic properties of Fe3O4@SiO2, Fe3O4@MSiO2 and the mesoporous silica shell nanozyme tags were studied using a vibrating sample strong magnetometer in the magnetic field range of -3000 to +3000 Oe. Figure 2G The results show that the saturation magnetization values of the synthesized Fe3O4, Fe3O4@MSiO2 and Fe3O4@MSiO2@Pt are 64.8, 40.8 and 18.7 emu·g, respectively. -1Among them, Fe3O4@MSiO2 and Fe3O4@MSiO2@Pt NZs exhibited lower saturation magnetization compared with Fe3O4, which may be due to the magnetic shielding effect of SiO2 shell and Pt particles on the surface of Fe3O4. Nevertheless, Fe3O4@MSiO2@Pt can still show a fast response within 45 s under external magnetic field, thus ensuring fast and efficient magnetic separation and enrichment of target analytes from complex samples. Figure 2H The nitrogen adsorption-desorption isotherm and pore size distribution curve of Fe3O4@MSiO2 are shown; the isotherm follows the typical IV isotherm defined by Brunauer et al., proving the existence of a uniform mesoporous structure. According to the IUPAC classification of hysteresis loop types, the P / P0 of the Fe3O4@MSiO2 sample is between 0.9 and 1.0, showing an H3 type hysteresis loop, which is a typical feature of mesoporous materials. Fig.2I The energy dispersive X-ray spectroscopy (EDS) elemental mapping of Fe3O4@MSiO2@Pt is shown in the figure. Small-sized Pt (purple) and Si (green) are distributed overlappingly on the surface of Fe3O4 (red) (blue), proving that Fe3O4@MSiO2@Pt was successfully prepared.
[0153] III. Crystal structure and crystallinity characterization test results: Powder XRD was used to characterize the crystal structure and crystallinity of the material. Figure 2J As shown, the XRD pattern of Fe3O4@MSiO2@PtNZs matches well with the three standard reference cards, indicating that there are three main components in the composite material: Fe3O4, Pt and SiO2. Observing the diffraction curve of Fe3O4@MSiO2@Pt NZs, there is a weak diffraction peak at 21.273° corresponding to the (111) plane of Fe3O4. There is a weaker peak at 35.072°, which belongs to the (011) plane of SiO2. The strongest peak in the figure appears at 41.395°, which is mainly due to the dominant phase Fe3O4 of the (111) crystal plane. The diffraction peak at 46.644° is related to the (111) plane of doped Pt, and the diffraction peaks at 50.460°, 67.245° and 74.144° are related to the (400), (511) and (440) planes of Fe3O4, respectively. Finally, there is a peak at 64.386° attributed to the (201) plane of SiO2. Comparing the composite materials Fe3O4@MSiO2 and Fe3O4@MSiO2@Pt NZs, the core phase of Fe3O4 maintains the structural integrity; however, with the introduction of the mesoporous SiO2 layer, the XRD peak intensity related to Fe3O4 gradually decreases. Combined with the above HRTEM test results, it is proved that the present invention successfully prepared the Fe3O4@MSiO2@Pt nanocomposite material.
[0154] XPS was used to further detect the surface elements and their respective valence states. Figure 2K As shown, the high-resolution scan of the Fe 2p spectrum shows that Fe 2p 1 / 2 The peaks of Fe 2p 3 / 2 The peaks of the Pt 2p spectrum are 710.88 eV and 712.98 eV, confirming the formation of Fe3O4. The O 1s orbitals are located at 529.88 eV and 531.98 eV, respectively, which are attributed to -Fe-O- and -O-Si-O-, further proving the presence of Fe3O4 and SiO2 in the sample. In addition, the Si 2p spectrum peak is decomposed into two main components at 99.58 eV and 102.28 eV. The high-resolution spectrum of Pt shows that Pt 4f 5 / 2 and Pt 4f 7 / 2 The characteristic peaks on the orbitals are at 71.58 eV and 74.98 eV, respectively, proving the successful loading of Pt. These results indicate the successful synthesis of Fe3O4@MSiO2@Pt NZs.
[0155] Test Example 2 Catalytic performance test Test sample: the test sample provided in Example 1; Test results: from Figure 3 It can be seen that in the range of 0~600 μL, with the addition of H2PtCl6, the absorbance gradually increases. It is worth noting that when the amount of Pt precursor added is 600 μL, the catalytic efficiency is the best, but the magnetic recovery rate is the worst. Therefore, the amount of Pt precursor added is selected as 400 μL in subsequent experiments. The pH value has a significant effect on the activity of nanozyme POD, from Figure 4A It can be seen that Fe3O4@MSiO2@Pt NZs exhibits perfect POD-like activity in the range of pH = 2 to 6 (highest at pH = 4), and almost no activity in the range of pH = 7 to 12. Therefore, the Fe3O4@MSiO2@Pt NZs prepared by the present invention has the best POD-like activity in the DAB colorimetric detection system (pH = 4), making it an ultrasensitive biosensing nanozyme label.
[0156] Then, the kinetic analysis of Fe3O4@MSiO2@Pt NZs was carried out under the optimal catalytic conditions. Figure 4B , Figure 4C As shown in Figure 2, within the appropriate substrate concentration range, typical Michaelis-Menten kinetic curves were observed for both TMB and H2O2. It is an important indicator reflecting the affinity between an enzyme and its substrate. The lower the value, the stronger the affinity of the enzyme for the substrate. Compared with Fe3O4, when TMB (7.19 mM) and H2O2 (25.35 mM) were used as substrates, the affinity of Fe3O4@MSiO2@Pt NZs was The lower value indicates that the Fe3O4@MSiO2@Pt composite nanozyme has a stronger affinity. The possible reason is that the active center of Fe3O4 has only one iron ion, while Fe3O4@MSiO2@Pt NZs shows abundant catalytic active sites, which is enhanced by its porous structure. The value is higher than that of TMB, indicating that it has a higher affinity for TMB. They are 3.51×10 -8 and 2.67×10 -8 M.s -1 . These results confirm that Fe3O4@MSiO2@Pt NZs have superior POD-like activity and play a vital role in promoting signal amplification and enhancing the catalytic deposition of nanozymes. Subsequently, the catalytic mechanism of Fe3O4@MSiO2@Pt NZs was studied. The POD-like activity was verified by electron spin resonance (ESR) analysis. The generation of •OH was determined by ESR spectroscopy using 5,5-dimethyl-1-pyrroline N-oxide (DMPO) as a spin trap. Figure 4D As shown, Fe3O4@Pt, Fe3O4@SiO2@Pt, and Fe3O4@MSiO2@Pt all exhibited the characteristic quartet signal of DMPO-•OH (1:2:2:1), and Fe3O4@MSiO2@Pt produced the largest amount of reactive oxygen species (ROS) (•OH) in the DMPO system. Therefore, it is shown that the nanotag prepared by the present invention has higher POD-like activity.
[0157] Test Example 3 LFIA Influenza A Test Test sample: the test sample provided in Example 1; Test method: like Figure 5 As shown, the structure and workflow of Fe3O4@MSiO2@Pt-LFIA for influenza A detection are given, and the workflow is as follows: S1. Formation of Fe3O4@MSiO2@Pt-Flu A complex: 0.4 μL of the mesoporous silica shell nanozyme tag prepared in Example 1 was added to different concentrations of Flu A for enrichment, and the formed Fe3O4@MSiO2@Pt-Flu A complex was separated by a magnet.
[0158] S2. Qualitative analysis: Drop the Fe3O4@MSiO2@Pt-Flu A complex on the sample pad. Under the action of capillary, the complex moves along the direction of the absorbent pad. The Fe3O4@MSiO2@Pt-Flu A complex is combined with the capture monoclonal antibodies (mAbs) fixed on the T line to form a Fe3O4@MSiO2@Pt-Flu A-mAbs sandwich structure, producing a black band for initial qualitative analysis. The excess Fe3O4@MSiO2@Pt immunolabeled continues to flow forward and is captured on the quality control line.
[0159] S3, Quantitative analysis: After the run, the colorimetric amplification DAB solution was dropped onto the T line. Due to its excellent POD-like activity, the synthesized nanotag catalyzed the generation of brown precipitated oxidized DAB (ox-DAB). The colorimetric amplification results can be intuitively identified or quantitatively evaluated through photos taken with a smartphone, and then the grayscale intensity value corresponding to the test line area can be extracted using Image J.
[0160] Test Example 4 Optimization of LFIA strips Test sample: the sample provided in Test Example 3; Test method: To obtain the best color development conditions and sensitivity of Fe3O4@MSiO2@Pt-LFIA strips, several key parameters were optimized. First, the antibody concentrations on the T line (0.4, 0.8, 1, 1.5, and 2 mg mL -1 )( Fig. 6A ). It can be observed that the signal intensity corresponding to the test line increases with the increase in the concentration of influenza A detection antibodies. However, too high a concentration of antibody may lead to nonspecific adsorption on the T line. Therefore, the optimal antibody concentration was determined to be 1 mg mL -1 It was found that the number of Fe3O4@MSiO2@Pt tags directly affects the amount of antigen binding, thereby affecting the sensitivity of the LFIA test strip. Figure 6B As shown in Figure 6C, 0.4 µL of label is the best choice for antigen detection because it reduces T-line nonspecific phenomena and has the highest signal-to-noise ratio. In addition, the time of chromatographic reaction plays an important role in the efficiency of immune response. As shown in Figure 6C, when the time reaches 10 min, the signal-to-noise ratio reaches the highest and the expected detection sensitivity is achieved. Therefore, 10 min is selected as the optimal chromatographic reaction time.
[0161] Test Example 5 Performance test of LFIA test strips for detecting influenza A virus Test conditions: Optimized parameter conditions of Test Example 4.
[0162] Under the optimized conditions, the Fe3O4@MSiO2@Pt-LFIA test strips were tested for the concentration of Flu A-NP (0~100 ng·mL -1 ) was used to evaluate the detection performance in the presence of Fig. 7A As shown in Figure 2, as the concentration of Flu A-NP in C-LFIA decreases, the color of the T line gradually becomes lighter. The results show that without any instrument, the concentration as low as 1 ng mL can be detected visually. -1 ,Compare Figure 7C The commercial colloidal AuNP-based LFIA test strips (10 ng mL -1 ) is 10 times higher, which is due to the higher specific surface area of Fe3O4@MSiO2@Pt.
[0163] Catalytic colorimetry was used to perform qualitative and quantitative analysis of Flu A-NPs. Fig. 7A As shown, the colorimetric signal of CA-LFIA is 0.01 ng·mL -1 , compared with the pre-catalytic (1 ng·mL -1 ) was increased by 100 times. To further evaluate the sensitivity of Fe3O4@MSiO2@PtNZs, a composite nanozyme (Fe3O4@SiO2@PtNZs) without a mesoporous SiO2 layer was prepared under the same conditions for the detection of influenza A. Figure 7B As shown in the figure, the visual value of Fe3O4@SiO2@Pt-CA-LFIA is 1 ng mL-1, which is lower than that of Fe3O4@MSiO2@Pt-CA-LFIA (0.01 ng mL -1 ) is 100 times lower and only one order of magnitude higher than the sensitivity before catalysis.
[0164] The above results show that the high specific surface area of the prepared mesoporous structure can increase the loading of Pt particles and improve the POD-like activity of Fe3O4@MSiO2@Pt NZs. The catalytic reaction with DAB produces brown ox-DAB, which significantly amplifies the colorimetric signal intensity of the T line and improves the detection sensitivity. At the same time, the grayscale value of the area on the T line is extracted using Image J software. Fig.7D As shown in the figure, a calibration curve was established based on the colorimetric signal intensity of the T line and the concentration of Flu A-NP. The correlation coefficient (R 2 ) is 0.999. The limit of quantification of Fe3O4@MSiO2@Pt-LFIA is 0.0089 ng·mL -1 The calculations were performed using the method outlined in the IUPAC protocol (LOD = y blank +3×SD blank , where y blank is the average colorimetric signal intensity of the blank group, SD blankis the standard deviation of these groups). Fig. 7E As shown, the LOD is significantly 112 times lower than that of Fe3O4@SiO2@Pt-LFIA.
[0165] To evaluate the specificity of the assay, a range of other respiratory viruses were tested, including RSV, MERS-CoV, SARS-CoV, Flu-B, and COVID-19. Figure 7F As shown in the figure, the colorimetric and catalytic colorimetric signal intensities of these viruses on the C-LFIA and CA-LFIA strips were similar to those of the blank group, indicating that the Fe3O4@MSiO2@Pt-LFIA strips have high specificity. In order to better evaluate the repeatability of the test paper, the present invention used 5 independent experiments to test influenza A (0.01 and 1 ng·mL -1 ) were tested in parallel. Figure 7G It can be seen that the visualization results of the five groups of C-LFIA and CA-LFIA strips are similar, and the relative standard deviation (RSD) values of the five individual test strips are 2.4% and 1.3%, respectively, confirming that Fe3O4@MSiO2@Pt-LFIA has good reproducibility.
[0166] Test Example 6 Simulated clinical sample test Test method: Three concentrations (50, 5 and 0.05 ng·mL) were added to the throat swab samples of healthy people. -1 ) of Flu A-NP to simulate the recovery rate of samples at different target concentrations.
[0167] As shown in Table 1 below (Recovery rate of Flu A-NP in throat swab samples), the average recovery rate of throat swab samples ranged from 95.20% to 106.00%, and the coefficient of variation (CV) fluctuated between 3.62% and 4.32%.
[0168] Table 1
[0169] Test results: The inactivated H1N1 virus was detected by Fe3O4@MSiO2@Pt-LFIA, further verifying the practical analytical capability of the new biosensor. Fig. 8A As shown, the C-LFIA test result is 1×10 4 copies·mL -1 , CA-LFIA test result is 50 copies·mL -1 , the qualitative sensitivity is increased by 200 times. Figure 8BThe results of the fitting curve showed that the LOD of Fe3O4@MSiO2@Pt-LFIA for inactivating H1N1 virus particles was 33 copies·mL -1 .
[0170] In summary, the present invention establishes an ultrasensitive catalytic colorimetric sensing platform based on nanozyme tags with mesoporous silica shells. The nanozyme tags with mesoporous silica shells of the present invention have excellent magnetic separation ability and can directly capture and detect target molecules in complex matrices without any pretreatment. The specific surface area is increased by introducing a mesoporous SiO2 layer, thereby making it possible to enhance the POD-like activity of the composite nanozyme. Therefore, the Fe3O4@MSiO2@Pt-LFIA strip can provide conventional colorimetric and colorimetric amplification signals for the detection of influenza A virus and inactivated H1N1 virus in a wide linear range, provide colorimetric results for qualitative analysis, enhance 100 times more than the commercial LFIA strips based on AuNPs, and have ultrasensitive quantitative results. It is worth noting that the LFIA test strips of the present invention also show significant specificity, repeatability and high recovery in influenza virus detection. This "three-in-one" multifunctional mesoporous silica shell nanozyme tag can become a promising pretreatment-free POCT disease diagnostic tool with high sensitivity and accuracy.
[0171] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A nanozyme tag with a mesoporous silica shell, characterized in that: The mesoporous silica shell nanozyme tag comprises a Fe3O4 core and a mesoporous silica shell coated on the surface of the Fe3O4 core; The voids in the mesoporous silica shell are filled with Pt particles, and antibodies for detecting influenza A N protein are connected to the Pt particles via carboxyl alkane sulfide.
2. The nanozyme tag of mesoporous silica shell according to claim 1, characterized in that The particle size of the Fe3O4 core is 95-105 nm; and / or, the thickness of the mesoporous silica shell is 15 to 25 nm; And / or, the specific surface area of the mesoporous silica shell is 60-62 m 2 ·g -1 ; and / or, the average mesopore size of the mesoporous silica shell is 4.8-4.9 nm; And / or, the total pore volume of the mesoporous silica shell is 0.12-0.14 cm 3 ·g -1 .
3. The mesoporous silica shell nanozyme tag according to claim 1, characterized in that: The particle size of the Pt particles is 3-6 nm; And / or, the carboxyalkane sulfide is 11-mercaptoundecanoic acid.
4. A method for preparing a nanozyme tag of a mesoporous silica shell according to any one of claims 1 to 3, characterized in that: The preparation method comprises: (1) dispersing Fe3O4 nanoparticles in an ethanol aqueous solution containing a dispersant, performing a first ultrasonic treatment, adding a catalyst, performing a second ultrasonic treatment, adding an organic silicone grease solution, performing a third ultrasonic treatment, and then coating the surface of the Fe3O4 nanoparticles with a silica shell to obtain Fe3O4@SiO2; (2) resuspending the Fe3O4@SiO2 in an aqueous solution containing a dispersant, adding a base and stirring to etch the silica shell to form a mesoporous silica shell, and collecting the product by magnetic separation to obtain Fe3O4@MSiO2; (3) mixing the Fe3O4@MSiO2, dispersant and chloroplatinic acid in an ethanol aqueous solution, performing a first stirring, adding a reducing agent, and performing a second stirring to deposit Pt particles in the voids of the mesoporous silica shell to obtain Fe3O4@MSiO2@Pt nanozyme; (4) mixing the Fe3O4@MSiO2@Pt nanozyme and carboxyl alkane sulfide in ethanol and subjecting them to ultrasonic treatment to connect the carboxyl alkane sulfide to the Pt particles, thereby obtaining Fe3O4@MSiO2@Pt-MUA seeds; (5) Dispersing the Fe3O4@MSiO2@Pt-MUA seeds in MEST buffer, performing the first ultrasonic treatment, and adding N -hydroxysuccinimide solution and carbodiimide solution, perform a second ultrasonic treatment to obtain a mixture; disperse the mixture in PBS buffer, add influenza A N protein detection antibody, incubate, add bovine serum albumin solution to block non-binding sites, collect the product by a magnet, and obtain the nanozyme label of the mesoporous silica shell.
5. The method for preparing the nanozyme tag of mesoporous silica shell according to claim 4, characterized in that: In step (1), the dispersant is polyvinyl pyrrolidone K40; the catalyst is NH4OH; and the organic silicone grease is tetraethoxysilane; And / or, in step (1), the volume ratio of the Fe3O4 nanoparticles, ethanol and water is (0.4-0.8):(30-50):(3-7); wherein the volume mass ratio of the Fe3O4 nanoparticles and the dispersant is (0.4-0.8) mL:(10-30) mg; And / or, in step (1), the volume ratio of the Fe3O4 nanoparticles, the catalyst and the silicone grease solution is (1.7-3.7):(3.4-6.4):1; wherein the concentration of the silicone grease solution is 0.9-1.0 g·mL -1 ; And / or, in step (1), the power of the first ultrasonic treatment, the second ultrasonic treatment and the third ultrasonic treatment are each independently 60 to 100 W; And / or, in step (1), the first ultrasonic treatment time is 1 to 10 min; the second ultrasonic treatment time is 20 to 40 min; the third ultrasonic treatment time is 20 to 40 min; And / or, in step (1), the following post-treatment is also included: after washing the Fe3O4@SiO2 with ethanol, it is resuspended in ethanol; wherein the concentration of the Fe3O4@SiO2 is 5~10 μM.
6. The method for preparing the nanozyme tag of mesoporous silica shell according to claim 4, characterized in that: In step (2), the dispersant is polyvinyl pyrrolidone K15; the alkali is sodium hydroxide solution; And / or, in step (2), the mass ratio of the Fe3O4@SiO2, dispersant and alkali is 1:(40-60):(300-500); the volume ratio of the Fe3O4@SiO2 and water is 1:(1-5); And / or, the concentration of the sodium hydroxide solution is 0.25-0.35 g / mL; And / or, in step (2), the stirring speed is 500-550 rpm, and the stirring time is 4-8 h; And / or, step (2) further includes the following post-treatment: washing the Fe3O4@MSiO2 with water and ethanol.
7. The method for preparing the nanozyme tag of mesoporous silica shell according to claim 4, characterized in that: In step (3), the dispersant is polyvinyl pyrrolidone K40; the reducing agent is sodium borohydride; And / or, in step (3), the mass ratio of Fe3O4@MSiO2, reducing agent and chloroplatinic acid is 1:(6-7):(6-7); And / or, in step (3), the mass volume ratio of the Fe3O4@MSiO2 and the ethanol aqueous solution is (2-4) mg:(40-60) mL; wherein the volume ratio of the ethanol and water is (10-30):(20-40); And / or, in step (3), the rotation speeds of the first stirring and the second stirring are respectively 500-550 rpm; And / or, in step (3), the first stirring time is 10 to 20 min; the second stirring time is 10 to 30 min; And / or, in step (3), the following post-treatment is further included: washing the Fe3O4@MSiO2@Pt nanozyme with ethanol and then resuspending it in ethanol; Wherein, the volume ratio of the Fe3O4@MSiO2@Pt nanozyme and ethanol is 1:(1~5).
8. The method for preparing the nanozyme tag of mesoporous silica shell according to claim 4, characterized in that: In step (4), the carboxyl alkane sulfide is 11-mercaptoundecanoic acid; And / or, in step (4), the volume ratio of the Fe3O4@MSiO2@Pt nanozyme to the carboxyl alkane sulfide is (100-300):1; and / or, in step (4), the final concentration of the carboxyl alkane sulfide is 8-12 mM; And / or, in step (4), the power of the ultrasonic treatment is 60-100 W, and the time of the ultrasonic treatment is 0.5-2 h.
9. The method for preparing the nanozyme tag of mesoporous silica shell according to claim 4, characterized in that: In step (5), the Fe3O4@MSiO2@Pt-MUA seeds, N -The volume ratio of hydroxysuccinimide solution to carbodiimide solution is (150-250):1:(4-6); and / or, N -The concentration of hydroxysuccinimide solution is 90~110 mM; and / or, the concentration of the carbodiimide solution is 9-11 mM; And / or, in step (5), the volume ratio of the mixture, influenza A N protein detection antibody and bovine serum albumin is (330-334):1:(90-120); And / or, in step (5), the power of the first ultrasonic treatment and the second ultrasonic treatment are each independently 60 to 100 W; And / or, in step (5), the first ultrasonic treatment time is 20 to 40 seconds; the second ultrasonic treatment time is 10 to 20 minutes; And / or, in step (5), the incubation time is 140 to 160 min; And / or, step (5) further includes the following post-treatment: resuspending the product collected by the magnet in a PBST solution.
10. Use of the nanozyme tag with a mesoporous silica shell according to claim 1 or 2 in preparing a biosensor for detecting influenza A virus.
Citation Information
Patent Citations
Bio-sensitive chip as well as preparation method and use thereof
CN103472237A
Magnetic nano composite material as well as preparation method and application thereof
CN110813312A
Three-dimensional homogeneous filling type magnetic-noble metal composite nano-enzyme, novel crown antigen immunochromatography test paper thereof and application of three-dimensional homogeneous filling type magnetic-noble metal composite nano-enzyme
CN115060893A
Magnetic nanoparticle and method for amplifying signal in lateral flow analysis by using same
WO2019117518A1
